Almost human? A comparative case study on the social media presence of virtual influencers. Issue 155 (November 2021) - Arsenyan, Jbid; Mirowska, Agata
Highlights: Virtual agents are permeating and interacting on publicly visible human networks. We compare posting behavior of and user reactions to virtual and human influencers. The human-like virtual influencer seems to be penalized for her almost human appearance. Uncanny Valley is seen for positive reactions to the human-like virtual influencer. A reverse effect is observed for doubt and negative reactions. Abstract: As virtual agents become prevalent in many domains, virtual influencers have gone live on social media platforms, integrating human networks and interacting with users. Building on research on human-computer interactions, the Uncanny Valley hypothesis, and Computers Are Social Actors paradigm, this paper aims to investigate (1) virtual agents' similarity to humans in terms of behaviour in human networks and (2) reactions to human versus virtual agents in human networks where this interaction is publicly visible. We analyse the posting behaviour of and reactions to one human, one human-like virtual, and one anime-like virtual influencer active on a popular social media platform via text and emoji postings over an 11-month period. We find that, despite the general positive atmosphere of the platform, the human-like virtual influencer receives significantly lower positive reactions, providing evidence for the Uncanny Valley. Additional measures of negative reactions show a similar pattern. We discuss these results within the context of authenticity and social identity on social media, providing recommendations for the implementation of virtual influencers in human social networks.